SOCIAL MEDIA ADDICTION DAN FEAR OF MISSING OUT SEBAGAI FAKTOR PEMICU PHONE SNUBBING PADA MAHASISWA - Harman, Putri Veronica; Langelo, Wahyuny; Sumilat, Vervando (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2025)
Background: Technological advancement, particularly the widespread use of smartphones and social media applications, has significantly altered the way individuals communicate and interact socially. This shift has given rise to addictive behaviors toward social media and a growing prevalence of Fear of Missing Out (FoMO), which negatively impacts the quality of social interactions, especially among university students. Objective: This study aims to examine the relationship between social media addiction and fear of missing out as contributing factors to phone snubbing (phubbing) behavior among students.Methods: This research employed a quantitative approach with a cross-sectional design. The population consisted of all students (N = 454), and the sample was selected using purposive sampling, resulting in a total of 212 respondents. The instruments used were questionnaires, and data were analyzed using the chi-square statistical test. Results: The results showed no significant relationship between social media addiction and phubbing behavior (p = 0.709 ≥ 0.05). However, a significant relationship was found between fear of missing out and phubbing behavior (p = 0.000 < 0.05). Conclusion: The study concludes that social media addiction does not have a significant correlation with phubbing behavior. In contrast, fear of missing out is significantly associated with phubbing among students. Keywords: fear of missing out; phubbing; students; social media addiction.